Synthesis, photophysical and electrochemical characterization of terpyridine-functionalized dendritic oligothiophenes and their Ru(II) complexes - Mishra, Amaresh; Mena-Osteritz, Elena; Bäuerle, Peter (Beilstein Journal of Organic Chemistry, 2013)
Pd-catalyzed Sonogashira cross-coupling reactions were used to synthesize novel π-conjugated oligothienylene-ethynylene dendrons and their corresponding terpyridine-based ligands. Their complexation with Ru(II) led to interesting novel metallodendrimers with rich spectroscopic properties. All new compounds were fully characterized by 1H and 13C NMR, as well as MALDI–TOF mass spectra. Density functional theory (DFT) calculations performed on these complexes gave more insight into the molecular orbital distributions. Photophysical and electrochemical studies were carried out in order to elucidate structure–property relationships and the effect of the dendritic structure on the metal complexes. Photophysical studies of the complexes revealed broad absorption spectra covering from 250 to 600 nm and high molar extinction coefficients. The MLCT emission of these complexes were significantly red-shifted (up to 115 nm) compared to the parent [Ru(tpy)2]2+ complex.
Keywords: dendrons; electrochemistry; oligothiophene; spectroscopy; terpyridine